2013
DOI: 10.3109/00498254.2013.780671
|View full text |Cite
|
Sign up to set email alerts
|

The pre-clinical absorption, distribution, metabolism and excretion properties of IPI-926, an orally bioavailable antagonist of the hedgehog signal transduction pathway

Abstract: 1. IPI-926 is a novel semisynthetic cyclopamine derivative that is a potent and selective Smoothened inhibitor that blocks the hedgehog signal transduction pathway. 2. The in vivo clearance of IPI-926 is low in mouse and dog and moderate in monkey. The volume of distribution is high across species. Oral bioavailability ranges from moderate in monkey to high in mouse and dog. Predicted human clearance using simple allometry is low (24 L h(-1)), predicted volume of distribution is high (469 L) and predicted half… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Another derivative of cyclopamine is Saridegib (IPI-926), which has shown antitumor activity in models of medulloblastoma, ovarian cancer, chondrosarcoma, and osteosarcoma (138)(139)(140)(141)(142). There have been early stage clinical trials with Saridegib that have shown favorable pharmacodynamics and pharmacokinetics while having some antitumor activity toward solid tumors (143)(144)(145)(146). However, Saridegib was not recommended for further developing in patients with myelofibrosis or pancreatic cancer (145,147).…”
Section: Agents Targeting Smomentioning
confidence: 99%
“…Another derivative of cyclopamine is Saridegib (IPI-926), which has shown antitumor activity in models of medulloblastoma, ovarian cancer, chondrosarcoma, and osteosarcoma (138)(139)(140)(141)(142). There have been early stage clinical trials with Saridegib that have shown favorable pharmacodynamics and pharmacokinetics while having some antitumor activity toward solid tumors (143)(144)(145)(146). However, Saridegib was not recommended for further developing in patients with myelofibrosis or pancreatic cancer (145,147).…”
Section: Agents Targeting Smomentioning
confidence: 99%
“…56,57 The most promising targeted therapy, IPI-926, is a semisynthetic small-molecule inhibitor derivative of the alkaloid cyclopamine that inhibits the hedgehog pathway by binding to and inhibiting Smoothened and thus keeping Gli inactive. 58 Olive et al, 59 in an exciting preclinical study, showed IPI-926 enhanced perfusion of gemcitabine within the pancreatic tumor and improved survival. In this study, IPI-926 decreased collagen 1 in the stroma and proliferation of a-SMA stromal cells and transiently increased blood vessel density in the tumors using a KPC mouse model.…”
Section: Hedgehogmentioning
confidence: 99%
“…Interestingly, saridegib is active in cells with the D473H point mutation that renders them resistant to vismodegib [145]. Although saridegib showed desirable preclinical absorption, distribution, metabolism, and excretion properties [147], and a phase I study in adult patients with solid tumors demonstrated a good pharmacokinetic profile [148], it has been discontinued for lack of response [149,150].…”
Section: Smoothened Inhibitorsmentioning
confidence: 99%